Modular unmanned aerial vehicle platform design: Multi-objective evolutionary system method. (April 2022) - Zheng, Wenyi; Mehbodniya, Abolfazl; Neware, Rahul; Wawale, Surindar Gopalrao; Ganthia, Bibhu Prasad; Shabaz, Mohammad
Abstract: For the air quality data collection, a great potential is offered by unmanned aerial vehicles (UAV) with spatial and temporal resolutions. The fast scientific development has enabled the class production of UAVs cost effective in which civilian applications are serviced. A modular UAV-based platform design and development are the objectives of this study. The system comprises of five modules like the UAV, the ground station, sensors, data acquisition (DA) module, and the data fusion (DF) module. With adequate flight time, UAV platform can fly on pathways which are predetermined as shown by the results of data collection missions. The high precision data and air quality are collected through the system simultaneously. In a real manner, they are integrated and visualized. The UAV system power consumption is measured on ground and flight. The consumed current reached about 30 A when the UAV was in the air regardless the speed.